Práctica social del aborto inducido como estrategia de control del crecimiento poblacional - Zambrano Granda, Jordy Manuel (My University, 2019)
The general objective of the essay is to reflect on the potential of the social practice of induced abortion as a strategy to control population growth, based on the execution of a documentary methodology close to hermeneutics. interested in the generation of information that supports the sociological debate with greater scope and depth, without moralistic biases or a priori prejudices. Everything indicates that, from a sociological perspective, abortion as a recurrent social phenomenon must be treated under the co-ordinates of a deep and multidimensional approach, covering demographic aspects in relation to the social practice that embodies it. Overpopulation and its consequences, social disasters, are real facts that run over social structures in the past and the historical present of humanity, by breaking the fragile balance between available resources and existing population in a given society. The careful reading of the sources at our disposal allows us to conclude that if abortion continues to be penalized, with its consequent closure in hiding, the symbolic and material conditions will be produced and reproduced in order to face future harmful outcomes, such as: more poverty, more hunger, greater begging, increase in the number of members in families, precarization of public services, among others. Unfortunately, it is in the developing countries, where the negative effects generated by the asymmetry between available resources and opportunities and exponentially growing people and communities are further maximized.
El objetivo general del ensayo, consiste en Reflexionar acerca del potencial de la práctica social del aborto inducido como estrategia de control del crecimiento demográfico, a partir de la ejecución de una metodología documental próxima a la hermenéutica. interesó la generación de información que sustente el debate sociológico con mayor alcance y profundidad, sin sesgos moralistas ni prejuicios apriorísticos. Todo indica que, desde la perspectiva sociológica el aborto como fenómeno social recurrente debe ser tratado bajo las coordenadas de un enfoque profundo y multidimensional, que abarque aspectos demográficos en relación con la práctica social que lo encarna. La sobrepoblación y sus consecuencias, los nefastos sociales, son hechos reales que atropellan las estructuras sociales en el pasado y el presente histórico de la humanidad, al romper el frágil equilibrio entre recursos disponibles y población existente en una sociedad determinada. La lectura minuciosa de las fuentes a nuestra disposición permite concluir que, de seguirse penalizando el aborto, con su consecuente encierro en la clandestinidad, se estarán produciendo y reproduciendo las condiciones simbólicas y materiales de cara a futuros desenlaces nefastos, tales como: más pobreza, más hambre, mayor mendicidad, aumento en el número de integrantes en las familias, precarización de los servicios públicos, entre otros. Lamentablemente, es en los países en vías de desarrollo, donde se maximizan aún más los efectos negativos que generan la asimetría entre recursos y oportunidades disponibles y personas y comunidades en crecimiento exponencial.
Keywords: ABORTO; DEMOGRAFIA; REVOLUCION; REPRODUCTIVA